The Analysis on the Poverty Characteristics of Baby Boomers -Using Models of Panel Data- - Deokho Cho; Gil Hwan Park (European Regional Science Association (ERSA), 2013)
Population aging is directly related to the rise of the life expectancy and/or the declining of birth rates. The speeds of the population aging and declining of birth rates have dramatically been increasing and these problems have been grown big social issues. And they will gradually be developed into the social burdens and risks. Especially this notes the characteristics poverty of baby boomers and focuses on how to handle panel data. This study aims at figuring out the structural problems of the baby boomers poverty and suggesting some policy alternatives for them who are potential welfare demanders. Consequently, panel analysis model can handle the cross-sectional and longitudinal statistic mega data. It also implements the individual and group effect analysis following the time change.
Keywords: 330; proverty Baby Boomers Panel Analysis; Panel Data